2020
DOI: 10.1186/s12964-020-00643-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular vesicles in tumour microenvironment

Abstract: In recent years, it has been demonstrated that extracellular vesicles (EVs) can be released by almost all cell types, and detected in most body fluids. In the tumour microenvironment (TME), EVs serve as a transport medium for lipids, proteins, and nucleic acids. EVs participate in various steps involved in the development and progression of malignant tumours by initiating or suppressing various signalling pathways in recipient cells. Although tumour-derived EVs (T-EVs) are known for orchestrating tumour progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 260 publications
(333 reference statements)
0
47
0
Order By: Relevance
“…Similarly, cell-cell communication and cell migration are integral parts of many disease processes. One notable example is cancer, where exosomes and other EVs have been shown to drive multiple aspects of cancer metastasis, including promotion of cancer cell motility and invasiveness and seeding of premeta-static niches (Sato and Weaver, 2018;Tao and Guo, 2020;Wortzel et al, 2019).…”
Section: Evs In Cell Migration In Diseasementioning
confidence: 99%
“…Similarly, cell-cell communication and cell migration are integral parts of many disease processes. One notable example is cancer, where exosomes and other EVs have been shown to drive multiple aspects of cancer metastasis, including promotion of cancer cell motility and invasiveness and seeding of premeta-static niches (Sato and Weaver, 2018;Tao and Guo, 2020;Wortzel et al, 2019).…”
Section: Evs In Cell Migration In Diseasementioning
confidence: 99%
“…PMNs are pre-programmed by extracellular vesicles (EVs) released by the primary tumour - these are cell-derived, membranous structures containing proteins, lipids, messenger RNAs and microRNAs ( 21 , 22 ). MicroRNAs in particular are potent contributors to PMN formation, allowing malignancies to achieve remote ‘epigenetic regulation’ by altering gene expression in PMN cells to establish a pro-neoplastic milieu facilitating vascular permeability, angiogenesis and stromal degradation ( 5 , 23 , 24 ).…”
Section: Pathophysiologic Basis Of Postoperative Cancer Recurrencementioning
confidence: 99%
“…The TME is composed of a complex ecosystem containing diverse types of cells, including cancer cells, cancer-associated fibroblasts, endothelial cells, adipocytes, mesenchymal stem cells, immune cells such as macrophages, T cells, B cells, and infiltrated cytokines, as well as non-cellular components, such as micro vesicles, and the extracellular matrix as reviewed in [219][220][221][222]. Studies have indicated that the interaction between tumor cells, the neighboring cells, and immune cells moderates tumor growth, progression, and metastasis as reviewed in [223,224]. Studies carried out on tumor cell-derived EVs have shown that they play a significant role in regulating key signaling pathways to modulate the TME and, thus, tumor progression.…”
Section: Bacterial Extracellular Vesicles In the Tumor Microenvironmentmentioning
confidence: 99%